High Prevalence of Lactobacillus crispatus Dominated Vaginal Microbiome Among Kenyan Secondary School Girls: Negative Effects of Poor Quality Menstrual Hygiene Management and Sexual Activity - Mehta, Supriya D.; Zulaika, Garazi; Otieno, Fredrick O.; Nyothach, Elizabeth; Agingu, Walter; Bhaumik, Runa; Green, Stefan J.; van Eijk, Anna Maria; Kwaro, Daniel; Phillips-Howard, Penelope A. (Frontiers in Cellular and Infection Microbiology, 2021)
The vaginal microbiome (VMB) impacts numerous health outcomes, but evaluation among adolescents is limited. We characterized the VMB via 16S rRNA gene amplicon sequencing, and its association with Bacterial vaginosis (BV) and sexually transmitted infections (STIs; chlamydia, gonorrhea, trichomoniasis) among 436 schoolgirls in Kenya, median age 16.9 years. BV and STI prevalence was 11.2% and 9.9%, respectively, with 17.6% of girls having any reproductive tract infection. Three community state types (CST) accounted for 95% of observations: CST-I L.crispatus-dominant (N=178, BV 0%, STI 2.8%, sexually active 21%); CST-III L.iners-dominant (N=152, BV 3.3%, STI 9.7%, sexually active 35%); CST-IV G.vaginalis-dominant (N=83, BV 51.8%, STI 25.3%, sexually active 43%). In multivariable adjusted analyses, sexual active girls had increased odds of CST-III and CST-IV, and use of cloth to manage menses had 2-fold increased odds of CST-IV. The predominance of L.crispatus-dominated VMB, substantially higher than observed in prior studies of young adult and adult women in sub-Saharan Africa, indicates that non-optimal VMB can be an acquired state. Interventions to maintain or re-constitute L.crispatus dominance should be considered even in adolescents.